Mozart KV 448 Menurunkan Densitas dan Aktivitas Neuroglia Hipokampus Mencit (Mus musculus) Selama Stres Prenatal No. 416-KE - Shelly Kusumarini; Lita Rakhma Yustinasari; Eka Pramystha Hestianah; Suryo Kuncorojati; Tutik Juniastuti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
The aim of this research was to explore the influence of Mozart KV 448 classical music therapy to the neuroglia cells of mice’s hippocampus that were exposed to stress during prenatal. This research were employing twenty female mices and twenty male mices. Female mices were estrus synchronized with PMSG and hCG then monomating to the males. Pregnant females were then divided into four groups (P0, P1, P2, P3). P0 was as control, P1 was treated by one minute forced swim test, P2 was treated by one minute forced swim test followed by thirtyminutes classical music Mozart KV 448 and P3 was treated by one minute forced swim test followed by sixty minutes classical music Mozart KV 448. This research was carried out for twenty-one days during gestation period. The neuroglia density result was analyzed using ANOVA and Duncan test. The neuroglia activity result wasanalyzed using Kruskal wallis test and Z test. The histology reading showed degradation of density and activity of hippocampus neuroglia.